2014
DOI: 10.1093/mollus/eyu023
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in the Trochulus hispidus complex and related taxa (Pulmonata: Hygromiidae): morphology, ecology and their relation to phylogeography

Abstract: In this study we investigated the morphology and ecology of representatives of the taxonomically ambiguous genus Trochulus. The main focus was on the T. hispidus complex, which comprises several genetically highly divergent mitochondrial clades, as determined in a parallel molecular genetic study. We analysed shell morphology and anatomical traits and asked whether the clades are differentiated in these characters. In addition, the related species T. oreinos and T. striolatus were investigated and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 20 publications
4
46
0
Order By: Relevance
“…Each snail was classified into two clusters, 1 and 2, six were assigned simultaneously to clusters 1 and 2, and one individual showed mixed affiliation to clusters 1 and 3, whereas the other was grouped to clusters 1, 2 and 3. Both here and in the results obtained by other authors [27], the taxonomic status of T . coelomphala remains unclear.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Each snail was classified into two clusters, 1 and 2, six were assigned simultaneously to clusters 1 and 2, and one individual showed mixed affiliation to clusters 1 and 3, whereas the other was grouped to clusters 1, 2 and 3. Both here and in the results obtained by other authors [27], the taxonomic status of T . coelomphala remains unclear.…”
Section: Discussionsupporting
confidence: 82%
“…hispidus complex were morphologically attributed to T . sericeus by Duda et al [27] and Kruckenhauser et al [16]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors not only found many morphologically unrecognized evolutionary lineages within this taxon, but also revealed that several alleged Zospeum species are ambiguously classified products of past taxonomic lumping traditions. However, in light of this past work, consideration of historical designations and recent investigations cannot ignore the fact that conventional molecular genetic methods, on the one hand, have not only solved many taxonomic conundrums in biological systematics, but have, on the other, also confounded the situation by uncovering more complicated patterns of unrecognized genetic variability, which otherwise, may never have been detected (Sauer and Hausdorf 2012, Jörger and Schrödl 2013, Duda et al 2014, for detailed discussion of cryptic speciation see Jörger and Schrödl 2013). Still, and in all due respect of this work, we strive for clarity and understanding of these microgastropods: for accuracy in biodiversity studies, for basic biogeographical investigations and for forming conservation strategies.…”
Section: Introductionmentioning
confidence: 99%